The Wisdom Value of Sanghyang Dedari in Short Film Media to Improve Student Character in Multicultural Studies Courses - Rupiana, I Nyoman Sugita; Suwindia, I Gede; Putra, I Nyoman Miarta (Indonesian Values and Character Education Journal, 2023)
The obstacle in lecture class learning is the difficulty of understanding the learning of the courses. So the right learning media is needed to overcome these problems. This study aims to develop learning media for short films based on the local wisdom of Sanghyang Dedari to improve student character in multicultural studies courses. This type of research is a research and development (RnD) method with a 4-D model design. The sample of this study was determined using a proportional random sampling technique so that a sample of 22 people was obtained. The research instrument used in this product trial was a questionnaire—data analysis techniques using quantitative and qualitative analysis. The pre-test results obtained the lowest score of 56 and the highest score of 77. Post-test results are the lowest score of 80 and the highest score of 92. The effectiveness test results show a significant difference seen from the significance number between the pre-test and post-test scores with a significance value (2-tailed) p equal to 0.000 less 0.05. Based on the results of Paired Sample T-Test testing shows that there is a significant difference between the results of character improvement in pre-test data and post-test data, so from these results, it can also be concluded that through the short film learning media method based on local wisdom Sanghyang Dedari can improve the results of improving student character in multicultural studies courses.